Plant Defense Responses Induced by Two Herbivores and Consequences for Whitefly Bemisia tabaci - Lin, Dan (Front Physiol, 2019)
Diverse herbivores are known to induce various plant defenses. The plant defenses may detrimentally affect the performance and preference to subsequent herbivores on the same plant, such as affecting another insect’s feeding, settling, growth or oviposition. Here, we report two herbivores (mealybug Phenacoccus solenopsis and carmine spider mite Tetranychus cinnabarinus) which were used to pre-infest the cucumber to explore the impact on the plants and the later-colonizing species, whitefly Bemisia tabaci. The results showed that the whiteflies tended to select the treatments pre-infested by the mites, rather than the uninfected treatments. However, the result of treatments pre-infested by the mealybugs was opposite. Total number of eggs laid of whiteflies was related to their feeding preference. The results also showed that T. cinnabarinus were more likely to activate plant jasmonic acid (JA) regulated genes, while mealybugs were more likely to activate key genes regulated by salicylic acid (SA). The different plant defense activities on cucumbers may be one of the essential factors that affects the preference of B. tabaci. Moreover, the digestive enzymes and protective enzymes of the whitefly might play a substantial regulatory role in its settling and oviposition ability.